Targeted Demethylation of the PLOD2 mRNA Inhibits the Proliferation and Migration of Renal Cell Carcinoma - Cao, Congcong; Ma, Qian; Huang, Xinbo; Li, Aolin; Liu, Jun; Ye, Jing; Gui, Yaoting (Frontiers in Molecular Biosciences, 2021)
N6‐methyladenosine (m6A) RNA modification is the most common internal mRNA modification in mammals and has been reported to play a key role in gene expression regulation. In this study, we detected a high level of m6A methylation of the PLOD2 3’-untranslated regions (3’UTR) in renal cell carcinoma (RCC). Furthermore, we found that the high expression level of PLOD2 was a prognostic indicator for patients with RCC. A dm6ACRISPR demethylation system was performed to accurately and specifically demethylate 3’UTR of PLOD2 and caused an inactivation of PLOD2 expression. Furthermore, we also performed many in vitro experiments to confirm that PLOD2 exerted tumor promoter effects by promoting tumor proliferation and migration. In conclusion, PLOD2 mRNA demethylated by dCas13b-ALKBH5 might provide a new light on the treatment for RCC.